Study on Risk Taking Behavior to HIV/AIDS Among Injecting Drug User’s in a Easter Region of Nepal - Bhatta, Bimala; Shah, Sashi Dev; Koirala, Nabaraj (Journal of Nobel Medical College, 2015)
Introduction: Drug abuse is the Universal Problem and Nepal is not the exception. Different study and report have reported high prevalence of HIV/AIDS among the IDUs in Nepal. According to the estimated data, there are eighty thousands drug addicts in Nepal and 50 % of them inject drugs through syringe. In Morang district, there are 1316 reported IDUs and 5000 to 7000 estimated IDUs. Objectives: To assess the risk taking behavior among IDUs with respect to needle syringe exchange and unprotected sex. Methodology: Cross sectional study design was applied to study the risk taking behavior among IDUs users in eastern region of Nepal. A non-probability, snowballing sampling technique was adopted. SPSS and Epi-Info was used to analyze the data of the study. Results: Majority of injecting drug users in eastern region were from the age group 21-30 years (62.7 %), unmarried (64.9 %) and living in nuclear family (80 %). Despite of the fact that most of the IDUs were unmarried most of them were sexually active (72.7 %). The study revealed that condom use during sexual intercourse was high (87.5 %) the consistent and regular use was low (57.5%). Sharing of syringe and reuse of needle was high among the IDUs i.e. 40 % of the respondent. In general the study had revealed that the harm reduction approaches among IDUs were low. Conclusion: The findings suggest that the majority of injecting drug users in eastern region were from the age group 21-30 years, unmarried and living in nuclear family. The study had further highlight that unsafe sex, sharing of syringe and needle and improper cleaning of needle and syringes before sharing is indication of unsafe behavior practices by IDUs. Finally, the study highlighted statistically significant relationship between HIV/AIDS knowledge and uses of condom during sexual intercourse and high rate of syringe sharing among married respondents. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.12233 Journal of Nobel Medical College Vol. 3, No.1 Issue 6, 2014, Page: 26-30